HIDDEN CURRICULUM: Upaya Peningkatan Kecerdasan Spiritual Siswa - Khairun Nisa (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2009)
The objective of the national education that has not been substantially achieved is developing generation who believe in one God and having a good character. Educational institutions expected to achieve this, in fact, focus only to students’ intellectual education. The moral education is neglected despite the fact the objective of national education is to develop students to be spiritually outstanding. It is recommended, therefore, that the application of education be evaluated thoroughly, and hidden curriculum could be a solution to this.